PHARMACEUTICAL PERFORMANCE IN THE EVALUATION AND ADHERENCE TO PHARMACOLOGICAL TREATMENT OF TYPE 2 DIABETES MELLITUS (REMUNOM, 2025)
Type 2 Diabetes mellitus is involved in important public health problems, implying high rates of morbidity and mortality. For people with diabetes, access to affordable treatments, including insulin and hypoglycemic agents, is essential for their survival. The main goal of type 2 diabetes treatment is blood sugar control, which helps prevent complications associated with the disease. The objective of the study is to characterize the role of the pharmacist in the evaluation and adherence to pharmacological treatment of DM2. The present study is an integrative review of the literature. To carry out the research in question, a review of the literature was carried out through scientific databases such as SciELO, BVS-Bireme, PUBMED, as well as on websites of official institutions, such as the Ministry of Health (MS). Furthermore, the search in the VHL was carried out involving the combined descriptors using Boolean operators: AND and OR. After searching the databases, 1097 titles were located by crossing descriptors. After analyzing the content and excluding studies due to divergence in thematic focus, only 8 studies met the eligibility criteria and were selected for analysis. It is noted that, as the health professional most accessible to the population, the pharmacist can have a great influence on adherence to treatment and its effectiveness, through guidance on the use of the drug, the importance of correctly following the medical prescription, reviewing the pharmacotherapy and thus avoiding undesirable effects, thus contributing to the improvement in the prognosis and quality of life of patients with DM2.